Proximity labeling to detect RNA–protein interactions in live cells - Lu, Mingxing (FEBS Open Bio, 2019)
RNA biology is orchestrated by the dynamic interactions of RNAs and RNA‐binding proteins (RBPs). In the present study, we describe a new method of proximity‐dependent protein labeling to detect RNA–protein interactions [RNA‐bound protein proximity labeling (RBPL)]. We selected the well‐studied RNA‐binding protein PUF to examine the current proximity labeling enzymes birA* and APEX2. A new version of birA*, BASU, was used to validate that the PUF protein binds its RNA motif. We further optimized the RBPL labeling system using an inducible expression system. The RBPL (λN‐BASU) labeling experiments exhibited high signal‐to‐noise ratios. We subsequently determined that RBPL (λN‐BASU) is more suitable than RBPL (λN‐APEX2) for the detection of RNA–protein interactions in live cells. Interestingly, our results also reveal that proximity labeling is probably capable of biotinylating proximate nascent peptide.